2007
DOI: 10.1590/s0004-28032007000100012
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of HBV-genotypes in immigrants affected by HBV-related chronic active hepatitis

Abstract: -Background -The genetic heterogeneity of the HBV genome has been established and eight genotypes can be classifi ed according to the criterion of ≥8% differences in the complete nucleotide sequence of the viral genome. Aims -To evaluate the prevalence of HBV-infection in a population of immigrants and to determine in patients with detectable serum HBV-DNA the HBV-genotypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 19 publications
(19 reference statements)
1
8
0
Order By: Relevance
“…On the other hand, positivity to markers of active HBV infection (acute or chronic carrier) among immigrants was equivalent to that reported in Spain [11], but it was about tenfold higher than that described in the Italian population (10.4% vs. 1.5%) [12], and also in other studies conducted in Southern Italy [13,14]. In our country, HBsAg positivity had a consistent downward trend over the past 30 years as a result of the improvement in the social-economical conditions, the decreased intrafamilial spread, a better knowledge of both transmission routes and prevention measures.…”
Section: Discussionsupporting
confidence: 52%
“…On the other hand, positivity to markers of active HBV infection (acute or chronic carrier) among immigrants was equivalent to that reported in Spain [11], but it was about tenfold higher than that described in the Italian population (10.4% vs. 1.5%) [12], and also in other studies conducted in Southern Italy [13,14]. In our country, HBsAg positivity had a consistent downward trend over the past 30 years as a result of the improvement in the social-economical conditions, the decreased intrafamilial spread, a better knowledge of both transmission routes and prevention measures.…”
Section: Discussionsupporting
confidence: 52%
“…This is the first study in Italy which evaluates the stage of HBV chronic hepatitis according to its viral genotype; previous studies had only showed the heterogeneity of the virus according to the subjects' geographical area [14, 15]. The results (HBsAg positive rate of 11.7%) reflect the actual prevalent migratory flow to Italy, especially in our geographic area, mostly represented by people coming from Africa [4].…”
Section: Discussionmentioning
confidence: 93%
“…Indeed, the rate of the interviewed undocumented migrants and refugees who agreed to be screened seems a useful parameter to evaluate the effectiveness of the screening. The success of screening to identify serum markers of HBV, HCV or HIV infection in undocumented migrants or refugees varies from one study to another, mainly due to the different composition of the populations studied according to their place of origin, legal status, length of stay in the foreign country and the quality of the strategies used to improve the access of these vulnerable populations to a screening programme [22][23][24][25][26][27][28][29][30][31]. In our study, individuals who were HBsAg positive, HBsAg negative/anti-HBc positive, anti-HCV positive and anti-HIV positive were referred to a tertiary-level clinical centre to complete the diagnostic course and if necessary to receive therapeutic follow-up.…”
Section: Discussionmentioning
confidence: 99%